Arsenic methylation, GSTO1 polymorphisms, and metabolic syndrome in an arseniasis endemic area of southwestern Taiwan - Chen, Jein-Wen; Wang, Shu-Li; Wang, Ya-Hui; Sun, Chien-Wen; Huang, Yeou-Lih; Chen, Chien-Jen; Li, Wan-Fen (Chemosphere (Oxford), 2012)
► MetS in relation to arsenic methylation was examined in a cohort with previous high exposure. ► Subjects with MetS experienced higher inorganic arsenic ingestion. ► Decreasing MMA ratio was associated with an increased risk for MetS. ► The increased risk for MetS was further modified by the GSTO1 A140D genotype. Previous studies have shown that hair arsenic (As) levels are associated with an increased prevalence of metabolic syndrome (MetS), which is a strong predictor for type 2 diabetes. The objective of this study was to evaluate whether urinary arsenic methylation is related to MetS in an arseniasis endemic area of southwestern Taiwan, taking genetic factors into account. Subjects were from a community-based cohort recruited in 1990 from three villages in Putai Township. In 2002–2003, we successfully followed 247 subjects and measured their urinary arsenic species including inorganic arsenic, monomethylarsonic acid (MMA) and dimethylarsinic acid (DMA), as well as the coding region polymorphisms of three genes known to involve in arsenic methylation. Results showed that subjects of MetS had a history of consuming well water of higher arsenic concentration as compared to those without MetS. We also found a significant association between urinary arsenic species and risk for MetS, where the odds ratio of MetS was increased with decreasing proportion of MMA and low rate of primary methylation (defined as MMA/inorganic As). The increased risk associated with low primary methylation rate was further modified by the GSTO1 A140D polymorphism, with the D allele carriers showing a slightly higher risk for MetS. Our results suggest that a low MMA% is associated with increased risk for MetS among As-exposed subjects and the genetic polymorphism of GSTO1, an enzyme responsible for the reduction of pentavalent arsenic species, may also play a modest modification role.